2013
DOI: 10.1002/pbc.24801
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell therapy and aerosol interleukin‐2 for the treatment of osteosarcoma lung metastasis

Abstract: PURPOSE Survival of patients with osteosarcoma lung metastases has not improved in 20 years. We evaluated the efficacy of combining natural killer [NK] cells with aerosol interleukin-2 [IL-2] to achieve organ-specific NK cell migration and expansion in the metastatic organ, and to decrease toxicity associated with systemic IL-2. EXPERIMENTAL DESIGN Five human osteosarcoma cell lines and 103 patient samples (47 primary and 56 metastatic) were analyzed for NKG2D ligand [NKG2DL] expression. Therapeutic efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…As several of the currently used chemotherapeutic drugs, as well as ionizing irradiation act via the DNA damage response pathway, a mild preconditioning using these drugs and/or local ionizing irradiation might sensitize tumor cells to immune recognition, leading to synergistic antitumor effects. These observations are in agreement with one previous report [27] but are in contrast with one that showed that DNAM-1 receptor also had a main role in NK cells' cytotoxicity against OS [28]. In vivo, OS primary and metastatic tumors have been shown to lose or downregulate HLA class I expression, thus becoming more susceptible to NK cell killing [29].…”
Section: Discussionsupporting
confidence: 72%
“…As several of the currently used chemotherapeutic drugs, as well as ionizing irradiation act via the DNA damage response pathway, a mild preconditioning using these drugs and/or local ionizing irradiation might sensitize tumor cells to immune recognition, leading to synergistic antitumor effects. These observations are in agreement with one previous report [27] but are in contrast with one that showed that DNAM-1 receptor also had a main role in NK cells' cytotoxicity against OS [28]. In vivo, OS primary and metastatic tumors have been shown to lose or downregulate HLA class I expression, thus becoming more susceptible to NK cell killing [29].…”
Section: Discussionsupporting
confidence: 72%
“…Osteosarcoma is a progressive and fatal malignant bone tumor with a nearly unchanged case fatality rate (23). At present, the majority of studies advocate the comprehensive treatment of osteosarcoma, including the use of surgery, radiotherapy, chemotherapy and immune therapy (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Guma et al (34) demonstrated that aerosol IL-2 treatment may increase lung NK cell numbers via stimulation of local NK cell proliferation, and this proliferation was observed to be organ specific, without IL-2-associated systemic toxicities. In addition, the therapeutic efficacy of aerosol treatment with IL-2+NK cells in inducing metastatic regression and increasing overall survival was observed to be higher, compared with aerosol IL-2 treatment alone or treatment with NK cells without aerosol IL-2 (34,35). In a murine OS transplantation model, an intraperitoneal injection of IL-2 monoclonal antibody was administered (S4B6) into mice that had received transplanted LM8 osteosarcoma cells, and it was identified that the number of pulmonary metastatic colonies and tumor size were significantly reduced (36).…”
Section: Strategies and Developments Of Immunotherapies In Osteosarcomentioning
confidence: 99%